The problem of forming professional competence with the help of the russian language practical courses based on a course “In the world of PR” - Petrov, Alexandr (2021)
The article proves that formation of professional competence with the help of the Russian language is a daunting challenge which the professors of Russian as a foreign language often face. Professional competence is a complex construct including communicative competence. The matter is that the PR specialists’ professional activity presupposes a wide range of business communications strategies, as well as different types of communication and leverage.